Implications of Formal and Non Formal Islamic Education Institutions in Indonesia on Children's Experience - Hanifah, Umi; Sujanah, Inu; Rohmawati, Anis Nur Diah; Maisyanah, Maisyanah (Journal of Islam and Science, 2020)
Education is not a strange thing anymore. After the establishment of schools for the people of Indonesia, then develop and become several levels and some parts in education. Not only schools are educational for children, but education is divided into formal education, Non-Formal education, and InFormal education. Formal education is also divided into several levels. There are an elementary school or Madrasah Ibtidaiyah, Junior High School or Madrasah Tsanawiyah, vocational or secondary middle school, or Madrasah Aliyah. In non-formal education, there are various types and levels, informal learning that comes from the community or the surrounding environment, education such as Koran in mosques, and diverse other non-formal education, which now has many pursuivants in the community. Often we find the understanding of general and specific education, such as Islamic education, that education is a process that is done to change one's behavior (morality) to be better. The method of education does not serve as formal education. Some aspects need to be completed through non-formal education such as Akhlakul Karimah, deepen the knowledge of religion and hone the skills that have been able to develop it as a useful thing. Formal educational education that is implemented deliberately planned and systematic to help prepare students' potential and non-formal education is present as complementary, reinforcing, and upbringing of its formal education. In the implementation of education, the process should be neatly packaged and supported by a positive environment. Thus the results achieved are as expected.